UDC 631.3 ANALYSIS OF THE INDICATORS OF THE AVERAGE SPEED OF UNITS FOR THE PROCESS OF LOADING INTO A POTATO HARVESTING MACHINE . - muminov, azam; Bayboboev, Nabijan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This paper examines the study of stationarity at different values of aggregate velocity during the transfer of lump mass and soil mixture and provides general conclusions.